Topographic attributes and Landsat7 data in the digital soil mapping using neural networks - Chagas, Cesar da Silva; Filho, Elpídio Inácio Fernandes; Vieira, Carlos Antônio Oliveira; Schaefer, Carlos Ernesto Gonçalves Reynaud; Júnior, Waldir de Carvalho (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this study was to evaluate discriminant variables in digital soil mapping using artificial neural networks. The topographic attributes elevation, slope, aspect, plan curvature and topographic index, derived from a digital elevation model, and the indexes of clay minerals, iron oxide and normalized difference vegetation, derived from a Landsat7 image, were combined and evaluated for their ability to discriminate soils of an area at the northwest of Rio de Janeiro State. The Java neural simulator and the backpropagation learning algorithm were used. The maps generated by each of the six tested sets of variables were compared with reference points for determining the rating accuracy. This comparison showed that the map produced with the use of all the variables reached a performance (73.81% of agreement) superior to maps produced by other sets of variables. Possible sources of error in the use of this approach are mainly related to the great lithological heterogeneity of the area, which hindered the establishment of a more realistic model of environmental correlation. The approach can help make the soil survey in Brazil faster and less subjective.